Uji bakteriologis air di PDAM GT Kabupaten Magelang dengan metode MPN Quanty-Tray - Lailatul Mubarokhah; Wijanarka Wijanarka (Jurusan Biologi FMIPA Universitas Cenderawasih, 2019)
Water is the main need for life. The bacteriological requirements for clean water are the presence or absence of Coliform bacteria and E. coli in water. The purpose of this study was to determine the quality of water from gravity springs and pump springs as a source of water in Magelang Regency PDAM GT and Magelang Regency community. This study was to finding out the bacteriological test of water in Magelang Regency PGT. This study was to know bacteriological water testing techniques using the MPN Quanti-method Tray in Magelang Regency PGT. The method used in this study is the Quanty-Tray Most Probable Number (MPN) method. The sample of this study were two gravitational springs namely Sample A and Sample B and two pumping springs namely Sample C and Sample D. The results of MPN calculations from the four springs did not meet the requirements of clean water ready to be distributed to the community because Coliform in the spring gravity water and pumps and found E. coli in the pump spring water. Key words: coliform, MPN quanty-tray, bacteriological requirement.